FBP1 /miR-24-1/enhancer axis activation blocks renal cell carcinoma progression via Warburg effect - Ju, Dongen; Liang, Ying; Hou, Guangdong; Zheng, Wanxiang; Zhang, Geng; Dun, Xinlong; Wei, Di; Yan, Fei; Zhang, Lei; Lai, Dong; Yuan, Jiarui; Zheng, Yu; et al. (Frontiers in Oncology, 2022)
Warburg effect is a pivotal hallmark of cancers and appears prevalently in renal cell carcinoma (RCC). FBP1 plays a negative role in Warburg effect as a rate-limiting enzyme in gluconeogenesis, yet its mechanism in RCC remains to be further characterized. Herein, we revealed that FBP1 was downregulated in RCC tissue samples and was related to the poor survival rate of RCC. Strikingly, miR-24-1 whose DNA locus is overlapped with enhancer region chr9:95084940-95087024 was closely linked with the depletion of FBP1 in RCC. Of note, miRNAs like miR-24-1 whose DNA loci are enriched with H3K27ac and H3K4me1 modifications are belonging to nuclear activating miRNAs (NamiRNAs), which surprisingly upregulate target genes in RCC through enhancer beyond the conventional role of repressing target gene expression. Moreover, miR-24-1 reactivated the expression of FBP1 to suppress Warburg effect in RCC cells, and subsequently inhibited proliferation and metastasis of RCC cells. In mechanism, the activating role of miR-24-1 was dependent on enhancer integrity by dual luciferase reporter assay and CRISPR/Cas9 system. Ultimately, animal assay in vivo validated the suppressive function of FBP1 on 786-O and ACHN cells. Collectively, the current study highlighted that activation of FBP1 by enhancer-overlapped miR-24-1 is capable of contributing to Warburg effect repression through which RCC progression is robustly blocked, providing an alternative mechanism for RCC development and as well implying a potential clue for RCC treatment strategy.